2021
DOI: 10.2147/ijgm.s298591
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Endoscopic Transforaminal Lumbar Interbody Fusion: Technique Note and Comparison of Early Outcomes with Minimally Invasive Transforaminal Lumbar Interbody Fusion for Lumbar Spondylolisthesis

Abstract: Purpose To compare the preliminary postoperative outcomes of percutaneous endoscopic transforaminal lumbar interbody fusion (Endo-TLIF) and minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) in the treatment of lumbar spondylolisthesis. Methods Sixty-two patients with single-segment lumbar spondylolisthesis received Endo-TLIF and MIS-TLIF were enrolled in present study. Perioperative parameters, including operation time, estimated blood loss (EBL), int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 25 publications
0
57
1
Order By: Relevance
“… 7 Compared with the minimally invasive TILF (MIS-TLIF), Endo-TLIF demonstrated better outcomes and faster recovery time after operation, owing to less invasion. 13 , 27 In fact, the transforaminal approach must face the following challenges: exiting nerve roots injury and inadequately contralateral decompression, which have been determined by the anatomical structure. In a retrospective research, the TESSYS-ISEE technique was employed to remove the dorsal and ventral structures around the involved nerve root, which achieved 270-degree spinal canal decompression.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Compared with the minimally invasive TILF (MIS-TLIF), Endo-TLIF demonstrated better outcomes and faster recovery time after operation, owing to less invasion. 13 , 27 In fact, the transforaminal approach must face the following challenges: exiting nerve roots injury and inadequately contralateral decompression, which have been determined by the anatomical structure. In a retrospective research, the TESSYS-ISEE technique was employed to remove the dorsal and ventral structures around the involved nerve root, which achieved 270-degree spinal canal decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these potential advantages, it remained unclear if PE-LIF had advantages for managing intervertebral space. Some scholars believe that with the endoscopic surgical technique, surgeons can handle the endplates under direct vision and determine adequate cartilage endplate removal ( 27 ). This may theoretically promote interbody fusion and reduce the risk of cage collapse.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have mainly focused on nano-hydroxyapatite/polyamide-66 Cage (n-HA/PA66) and Polyetheretherketone (PEEK), which have been widely recognized. Recent studies have suggested that the titanium expandable cage can reduce nerve roots injury, restore lumbar lordosis, and achieve indirect decompression of the spinal canal and intervertebral foramen ( 22 , 27 ). However, the potential complications of bone endplate injury and pseudarthrosis could not be ignored during these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome MIS-TLIF shortcomings, percutaneous endoscopic TLIF (PE-TLIF) has been commonly used for patients with LDD [11][12][13]. PE-TLIF makes possible a complete endoscopic discectomy, spinal canal and foramina decompression, and interbody fusion via the endoscopic and working portal [14][15][16][17]. Although numerous earlier investigations explored the relative efficacies of PE-TLIF and MIS-TLIF in treating LDD [11][12][13][14][15][16][17][18], most of these studies were retrospective in nature.…”
Section: Introductionmentioning
confidence: 99%
“…PE-TLIF makes possible a complete endoscopic discectomy, spinal canal and foramina decompression, and interbody fusion via the endoscopic and working portal [14][15][16][17]. Although numerous earlier investigations explored the relative efficacies of PE-TLIF and MIS-TLIF in treating LDD [11][12][13][14][15][16][17][18], most of these studies were retrospective in nature. Since multiple factors can sway the outcomes of a retrospective investigation, and introduce unintentional bias, a meta-analysis is recommended to extensively evaluate relevant literature, reduce bias risk, and enhance the overall statistical power of the collective study outcomes.…”
Section: Introductionmentioning
confidence: 99%